Injectable Hydrogel Combined with Nucleus Pulposus-Derived Mesenchymal Stem Cells for the Treatment of Degenerative Intervertebral Disc in Rats. (15th October 2019) - Wang, Feng; Nan, Li-ping; Zhou, Shi-feng; Liu, Yang; Wang, Ze-yu; Wang, Jing-cheng; Feng, Xin-min; Zhang, Liang
Abstract : Stem cell-based tissue engineering in treating intervertebral disc (IVD) degeneration is promising. An appropriate cell scaffold can maintain the viability and function of transplanted cells. Injectable hydrogel has the potential to be an appropriate cell scaffold as it can mimic the condition of the natural extracellular matrix (ECM) of nucleus pulposus (NP) and provide binding sites for cells. This study was aimed at investigating the effect of injectable hydrogel-loaded NP-derived mesenchymal stem cells (NPMSC) for the treatment of IVD degeneration (IDD) in rats. In this study, we selected injectable 3D-RGD peptide-modified polysaccharide hydrogel as a cell transplantation scaffold. In vitro, the biocompatibility, microstructure, and induced differentiation effect on NPMSC of the hydrogel were studied. In vivo, the regenerative effect of hydrogel-loaded NPMSC on degenerated NP in a rat model was evaluated. The results showed that NPMSC was biocompatible and able to induce differentiation in hydrogel in vivo. The disc height index (almost 87%) and MRI index (3313.83 ± 227.79 ) of the hydrogel-loaded NPMSC group were significantly higher than those of other groups at 8 weeks after injection. Histological staining and immunofluorescence showed that the hydrogel-loaded NPMSC also partly restored the structure and ECM content of degenerated NP after 8 weeks. Moreover, the hydrogel could support long-term NPMSC survival and decrease cell apoptosis rate of the rat IVD. In conclusion, injectable hydrogel-loaded NPMSC transplantation can delay the level of IDD and promote the regeneration of the degenerative IVD in the rat model.